2022
DOI: 10.1007/s11356-022-19927-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring and potential health risk assessment from Pymetrozine exposure among communities in typical rice-growing areas of China

Abstract: Pymetrozine is one of the most common insecticides used in China. This study was conducted to analyse Pymetrozine's potential exposures through various environmental routes beyond the treatment area. The aim was to estimate the potential health risk for communities due to non-dietary exposure to Pymetrozine in soil and paddy water. Data on registration of pesticides in China, government reports, questionnaires, interviews, literature reviews as well as toxicological health investigations were evaluated to dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Tudi. et al [12] discussed the potential chronic health risk of pymetrozine in soil and water in typical rice-growing areas of China; the results showed that the potential lifetime non-cancer risks associated with soil exposure for adults in both areas were higher than the potential non-cancer lifetime risks associated with dermal contact with paddy water. The potential non-cancer lifetime risks associated with soil exposure for adults in both areas were lower than the potential non-cancer lifetime risks associated with ingestion exposure to soil in both areas.…”
Section: Chronic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Tudi. et al [12] discussed the potential chronic health risk of pymetrozine in soil and water in typical rice-growing areas of China; the results showed that the potential lifetime non-cancer risks associated with soil exposure for adults in both areas were higher than the potential non-cancer lifetime risks associated with dermal contact with paddy water. The potential non-cancer lifetime risks associated with soil exposure for adults in both areas were lower than the potential non-cancer lifetime risks associated with ingestion exposure to soil in both areas.…”
Section: Chronic Diseasementioning
confidence: 99%
“…Equipment for appropriate pesticide application is important for application efficiency [9] to minimize the loss of spray solution as well as reduce pesticide residuals in the environment and adverse human health effects due to over-spraying and residues. Humans are directly exposed to pesticides in the workplace [10] and indirectly through environmental media, such as air, water, soil, and the food chain, which may be contaminated with pesticides [11,12]. Dermal, oral, and respiratory routes are the main common pathways by which pesticides enter the human body [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information on the cancer risk posed by pymetrozine for food products. Based on Tudi et al, (30), the potential total cancer risk due to ingestion and skin exposure via soil and paddy water for people of Guangxi and Hunan Province was estimated to be less than 1x10 −6 .…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Previous studies on the contamination, exposure, and health risk assessment of Pymetrozine via environmental routes [20,21,24,[106][107][108][109][110] are described in the following paragraphs. [24] carried out field trials in supervised rice fields in Zhejiang, Anhui, and Beijing for two consecutive years.…”
Section: Pymetrozinementioning
confidence: 99%
“…However, because organophosphorus pesticides are extensively used, they enter the natural environment and pollute water, soil, and sediments [19], posing a high potential risk to wildlife and human health [20]. Consequently, it was banned by the Chinese government in 2018 [21]. Currently, Pymetrozine and Avermectin have replaced toxic organophosphorus insecticides (Chlorpyrifos), which were previously used on rice crops in China [7,17,[22][23][24][25][26][27][28] and continue to be used in some other countries of the world [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%